Learning from the Chinese Miracle : Development Lessons for Sub-Saharan Africa - Zafar, Ali (2012)
A notable contrast in modern economic history has been the rapid economic growth of China and the slower and volatile economic growth in Sub-Saharan Africa. As the engagement between the two continues to grows, there will be a greater cross-fertilization of experiences. Total factor productivity comparisons suggest that capital accumulation in China coupled with more efficient factor usage explains the differential with Africa. Although the two have similar populations and patterns of inequality, their growth trajectories have been divergent. What can Africa learn from China? Although the lessons vary depending on country location and resource endowment, seven basic lessons are visible. First, the political economy of Chinese reforms and the shared gains between political elites and the private sector can be partially transplanted to the African context. Second, the Chinese used diaspora capital and knowledge in the early reform years. Third, rural reforms in China helped accelerate economic takeoff through a restructuring of property rights and a boost to both savings rates and output. Fourth, Chinese growth has taken place in the context of a competitive exchange rate. Five, port governance in China has been exemplary, and African landlocked economies can benefit significantly from port reform in the coastal countries. Six, China has experimented with a degree of decentralization that could yield benefits for many Sub-Saharan African countries. Seventh, Africa can learn from China s policies toward autonomous areas and ethnic minorities to stave off conflict. Africa can learn from China s experiences and conduct developmental experiments for poverty alleviation goals.